Mycorrhizal symbiosis and natural dye waste organic fertilizer: Enhancing growth and yield in Indigofera tinctoria - Arista, Nor Isnaeni Dwi; Budiastuti, Maria Theresia Sri; Supriyono; Nurmalasari, Aprilia Ike; Setyaningrum, Desy; Manurung, Ida Rumia (Journal of Earth Kingdom, 2024)
Background: Indigofera tinctoria, commonly known as true indigo, is a plant widely used in the textile industry for its natural indigo dye, which produces a rich blue color for fabrics. I. tinctoria, known for its natural bluish-purple dye, generates 10% dye and 90% waste during extraction, requiring effective waste management. This study aimed to optimize organic fertilizer and mycorrhiza doses from I. tinctoria  waste for enhancing soil fertility in arid regions. Methods: The study was conducted from May to December 2020 in Puron Village, Bulu District, Sukoharjo Regency. A factorial Completely Randomized Block Design (CRBD) with 2 factors was employed. The first factor consisted of 5 levels of I. tinctoria  organic fertilizer treatments: 0, 100, 200, 300, and 400 g per plant. The second factor included 3 levels of mycorrhiza treatments: 0, 10, and 20 g per plant. Variables observed included mycorrhizal infection on roots, plant growth rate, and yield (fresh leaf and shoot weight of I. tinctoria ). Data analysis utilized ANOVA at a 5% significance level followed by Duncan Multiple Range Test (DMRT). Results: The results indicated that organic fertilizer from natural dye waste at a dosage of 200 g per plant increased the percentage of mycorrhizal-infected roots and boosted shoot weight by 63.27% at 8 weeks after planting (WAP). Mycorrhiza at 10 g per plant increased mycorrhizal infection percentage and enhanced shoot weight by 45.98% at 4 WAP. The combination of I. tinctoria  extraction waste organic fertilizer at 200 g per plant and mycorrhizal at 10 g per plant showed interaction, significantly increasing the growth of root nodules of I. tinctoria by 84.04% at 12 WAP. Conclusion: The integration of organic fertilizer derived from indigo dye waste and mycorrhiza presents a promising strategy for enhancing I. tinctoria  growth and productivity. Novelty/Originality of this Study: This study is distinctive in its demonstration of the effective use of I. tinctoria  extraction waste as an organic fertilizer, aligning with zero-waste principles and contributing to improvements in plant growth and soil fertility. Furthermore, it investigates the synergistic effects of mycorrhizal associations on enhancing nutrient absorption and overall productivity of I. tinctoria , an aspect that has not been thoroughly explored in prior research.